2015
DOI: 10.1530/erc-14-0351
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor heterogeneity and clonal evolution in an aggressive papillary thyroid cancer and matched metastases

Abstract: The contribution of intratumor heterogeneity to thyroid metastatic cancers is still unknown. The clonal relationships between the primary thyroid tumors and lymph nodes (LN) or distant metastases are also poorly understood. The objective of this study was to determine the phylogenetic relationships between matched primary thyroid tumors and metastases. We searched for non-synonymous single-nucleotide variants (nsSNVs), gene fusions, alternative transcripts, and loss of heterozygosity (LOH) by paired-end massiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…However, only 33–40% of multifocal PTC cases showed a discordant BRAF status between foci [57]. To determine the phylogenetic relationships between matched primary thyroid tumours and metastases, Le Pennec et al [58] performed paired-end massively parallel sequencing of 2 areas of the primary tumour, including 1 pleural metastasis (PLM) and 2 LNMs from a patient with aggressive PTC. Although all of the examined tissue samples were composed of several cellular subclones, the analysed areas of the primary tumour and one of the LNMs displayed similar genetic profiles, whereas the other LNM presented more divergent mutations and fusions.…”
Section: Phenotypic and Molecular Heterogeneity Of Tc Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only 33–40% of multifocal PTC cases showed a discordant BRAF status between foci [57]. To determine the phylogenetic relationships between matched primary thyroid tumours and metastases, Le Pennec et al [58] performed paired-end massively parallel sequencing of 2 areas of the primary tumour, including 1 pleural metastasis (PLM) and 2 LNMs from a patient with aggressive PTC. Although all of the examined tissue samples were composed of several cellular subclones, the analysed areas of the primary tumour and one of the LNMs displayed similar genetic profiles, whereas the other LNM presented more divergent mutations and fusions.…”
Section: Phenotypic and Molecular Heterogeneity Of Tc Subtypesmentioning
confidence: 99%
“…These data indicate that genetic alterations accumulate after clonal PLM separation from the primary clone. Although there is currently no clear answer as to whether cancer cells simultaneously spread from the primary thyroid tumour to the regional LNs and distant locations or first spread to the lymph node and then to further locations, Le Pennec et al [58] suggested that the PLM originated from a subclone of the LNM.…”
Section: Phenotypic and Molecular Heterogeneity Of Tc Subtypesmentioning
confidence: 99%
“…Despite increasing WDTC globally, few studies have investigated metastatic sites of WDTC from a genomic perspective. RNA-Seq analysis of metastatic sites, including two LNM and one pleural metastasis from a single patient, revealed intratumor heterogeneity and clonal evolution (32). Another miRNA study analyzed miRNA transcriptomes of PTC with four LNM and noted that downregulation of miRNAs was a common feature in PTC tumorigenesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…By the analysis of single nucleotide variants, gene fusions, and loss of heterozygosity, the authors showed that some of the genetic alterations were ubiquitously detected in all the tumor samples from the patient and others were detected only in some tumor areas, indicating the presence of several subclones in the neoplastic tissues. Interestingly, the two selected areas of the primary tumor and the two selected areas of on regional metastasis presented similar genetic profiles, whereas the two selected areas of another regional metastasis had more divergent mutations and fusions [55]. Striking heterogeneity was also observed between paired primary tumors and metastases in studies done by means of NGS and WES studies [58,60,63,64].…”
Section: Discordant Mutational Status Between Primary Site and Metastmentioning
confidence: 95%
“…Accordingly, in PTC the allelic frequency must be normalized for the percentage of tumor cells in the sample, a measurement not always easy to perform [22,29]. Indeed, the number of the studies included in the present review which report data on the genetic characterization and/or ITH in TC, not evaluating tumor purity [27, are significantly more numerous than those which normalized the data for the percentage of tumor cells [7,20,22,29,[53][54][55]. Thus, data on ITH obtained without considering the purity of the tumor must be considered with caution.…”
Section: Introductionmentioning
confidence: 99%